THE TRUTH RELATIONS IN THE MAIN CHARACTER’S ENTAILMENT SENTENCES IN MURDER ON THE ORIENT EXPRESS MOVIE - Febiyana Anisa (MEDIOVA: Journal of Islamic Media Studies, 2021)
This study analyzed entailment of the main character’s sentences in Murder on The Orient Express movie in the semantics field. The purpose of this study is to explain the truth in the sentence uttered by the main character in the movie and to prove the truth value from the interlocutor’s response in the sentence. This study focused on explaining the truth of Poirot’s sentences and proving the truth value from the interlocutor’s response. This study used a qualitative descriptive method and a propositional logic approach. This study found 16 data of entailment. The data were analyzed using the theory of entailment from Fasold and Saeed, and theory of logic from Goranko and Hurley. The entailment sentences are entered into the truth table which explains the truth value of the sentence accompanied by logical explanations which are divided into deductive and inductive arguments. The truth value of the entailment sentence can be seen through the response of the main character's interlocutors.